The Brazilian justice system addressed in supplementary material (paradidatic) for Integrated High School: concerns and possibilities (Research, Society and Development, 2022)
By consensus there is a general understanding that the crisis in the Brazilian prison system represents one of the main social problems in the recent history of the country. This article aims at presenting the investigative trajectory of the production of supplementary materials (paradidactic) that are a contribution to qualifying this debate at the Integrated High School level, directly creating a dialog with the programmed Sociology curriculum. This research has been developed in the Graduate Program in Professional and Technical Education (ProEPT/Ifal) using a qualitative methodology, of the Investigative-action-participative kind proposed by Fals Borda (1987). At first, we reviewed bibliographies and during the step for diagnose a questionnaire was used with the faculty of the Sociology department on several campi in Ifal, semi structured interviews were conducted with five of these professionals and the student body of the ‘Estradas’ course in Maceió also answered questionnaires. The interviews were conducted under the light of Bardin (2011) content analysis and charts were generated to better illustrate the data. From this datum, we built an early version of ‘Caderno Reflexivo’. This material has been validated by four researchers in this field and ten Sociology professors at Ifal. Our perception of the ‘Caderno’ is that this material can contribute to qualifying this discussion of our prison system as well as fostering critical thinking on the matter in classrooms, all of which represents an effort to overcome social inequalities, and that such efforts need to be promoted and encouraged.